Green Sustainable Process for Chemical and Environmental Engineering and Science : Methods for Producing Smart Packaging - Inamuddin; Altalhi, Tariq; Cruz, Jorddy Neves (Elsevier, 2023)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Methods for Producing Smart Packaging covers the latest advances in the development and production of smart packaging. The book addresses issues related to the production of smart packaging, including marketing and environmental impacts of these new products. The book demonstrates how modern packaging goes beyond protecting food against physical, chemical, and biological damage, and that scientific advances now enable producing functional packaging that prolongs product quality, preserves physical and chemical properties, produces greater protection against transportation shocks, and makes food more compact and easily recycled.